Characteristics of infective endocarditis according to the mode of acquisition – a single-center, retrospective analysis - B. Dobreva-Yatseva; F. Nikolov; R. Raycheva; I. Manolov; P. Nikolov; N. Ivanova; D. Iovanovska; I. Kuchmov; M. Tokmakova (Българска кардиология, 2023)
According to the mode of acquisition, infective endocarditis (IE) is classifi ed as community-acquired (CAIE), healthcareassociated (HAIE), and injection drug use–related IE (IDUIE). At this stage, there are no data for Bulgaria for these three groups of patients. Objective: We set ourselves the goal of investigating IE according to the mode of acquisition and to make a clinical-instrumental characterization of the groups. Material and methods: The study is single-center, retrospective and includes 270 patients treated at the UMHAT “Sveti Georgi” – Plovdiv for the period 01.2005-12. 2021. Results: Patients with CAIE were 64.8% (175), with HAIE 26.7% (72) and with IDUIE 8.5% (23). Patients with IDUIE are younger compared to the other two groups (33; 8 years) (p = 0.000), with low comorbidity (CCI – 1, IQR – 1; p = 0.000), with most frequent right-sided involvement (p < 0.001) and with the most common causative agent being Staphylococcus aureus (p < 0.01). Patients with HAIE were the oldest (69; 18 years;), with the most comorbidity (CCI – 4; IQR – 3), with no signifi cant difference with CAIE (66; 20 years; and CCI – 3; IQR – 3). The large proportion of portal of entry for them were manipulations/ procedures (62.5%) and hemodialysis (18.1%), with Enterococci being the most common causative agent (19.5%, p = 0.001). In-hospital mortality and early surgical intervention were without signifi cant difference in the three groups. Conclusion: Knowledge of the three groups of IE according to the mode of acquisition – CAIE, HAIE and IDUIE and their characteristics is important for the choice of initial empiric antibiotic treatment and for improvement of prevention.